2021
DOI: 10.1016/j.jbc.2021.100653
|View full text |Cite
|
Sign up to set email alerts
|

Design of novel peptide inhibitors against the conserved bacterial transcription terminator, Rho

Abstract: The transcription terminator Rho regulates many physiological processes in bacteria, such as antibiotic sensitivity, DNA repair, RNA remodeling, and so forth, and hence, is a potential antimicrobial target, which is unexplored. The bacteriophage P4 capsid protein, Psu, moonlights as a natural Rho antagonist. Here, we report the design of novel peptides based on the C-terminal region of Psu using phenotypic screening methods. The resultant 38-mer peptides, in addition to containing mutagenized Psu sequences, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 55 publications
(90 reference statements)
1
14
0
Order By: Relevance
“…1 B ). Earlier, we observed that up to eight amino acid deletions (peptide 33Δ8) from the CTD of peptide 33 did not affect its Rho-binding or cell growth inhibitory functions ( 10 ). The net charge of peptide 33 changes significantly upon CTD deletions, which in turn affects their functions.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…1 B ). Earlier, we observed that up to eight amino acid deletions (peptide 33Δ8) from the CTD of peptide 33 did not affect its Rho-binding or cell growth inhibitory functions ( 10 ). The net charge of peptide 33 changes significantly upon CTD deletions, which in turn affects their functions.…”
Section: Resultsmentioning
confidence: 95%
“…Psu’s solvent-exposed C-terminal domain (CTD) (helix 6 and helix 7) interacts directly with Rho, and its N-terminal domain stabilizes its structure ( 9 ). We cloned the C-terminal helix-7 in a suitable expressing vector and randomly mutagenized it to select clones that inhibit the functions of the Rho protein (( 10 ), Fig. S1 A ).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…While short peptides or lowmolecular-weight compounds will not support the dimerization of two open ρ rings akin to Psu, substances that bind to and increase the pitch of open ρ hexamers may conceivably allow expansion into inactive ρ filaments. Notably, Psu-derived, ρ-inhibiting peptides that are active in vivo have already been designed 75 , but the structural basis of their modes of action remains to be explored.…”
Section: Discussionmentioning
confidence: 99%